Oxytocin Reduces Intravesical Pressure in Anesthetized Female Rats: Action on Oxytocin Receptors of the Urinary Bladder - Cafarchio, Eduardo M.; da Silva, Luiz A.; Auresco, Luciana C.; Rodart, Itatiana F.; de Souza, Janaina S.; Antonio, Bruno B.; Venancio, Daniel P.; Maifrino, Laura B. M.; Maciel, Rui M. B.; Giannocco, Gisele; Aronsson, Patrik; Sato, Monica A. (Frontiers in Physiology, 2020)
Urinary bladder dysfunction affects several people worldwide and shows higher prevalence in women. Micturition is dependent on the Barrington´s nucleus, pontine urine storage center and periaqueductal gray matter, but other brain stem areas are involved in the bladder regulation. Neurons in the medulla oblongata send projections to hypothalamic nuclei as the supraoptic nucleus, which synthetizes oxytocin and in its turn, this peptide is released in the circulation. We investigated the effects of intravenous injection of oxytocin (OT) on the urinary bladder in sham and ovariectomized rats. We also evaluated the topical (in situ) action of OT on intravesical pressure (IP) as well as the existence of oxytocin receptors in the urinary bladder. In sham female Wistar rats, anesthetized with isoflurane, intravenous infusion of OT (10 ng/kg) significantly decreased the IP (-47.5±1.2%) compared to saline (3.4±0.7 %). Similar effect in IP was observed in ovariectomized rats after i.v. OT (- 41.9±2.9%) compared to saline (0.5±0.6 %). Topical administration (in situ) of 0.1 mL of OT (1.0 ng/mL) significantly reduced the IP (22.3.0±0.6%) compared to saline (0.9±0.7 %). We also found by qPCR that the gene expression of oxytocin receptor is present in this tissue. Blockade of oxytocin receptors significantly attenuated the reduction in IP evoked by oxytocin i.v. or in situ. Therefore, the findings suggest that 1) intravenous oxytocin decreases intravesical pressure due to bladder relaxation and 2) OT has local bladder effect, binding directly in receptors located in the bladder.